PEMANFAATAN API PADA APLIKASI PORTAL BERITA SEDERHANA - Sulistyo, Henny Wahyu; Oktavianto, Hardian; Arifin, Zainul; Wardoyo, Ari Eko; Fitriyah, Nur Qodariyah (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2024)
Mobile applications, especially those that function as a medium for notification to users, are increasingly developing, from previously only being website-based, now increasingly being mobile-based. The public's need for applications that can provide news or information that is considered important is also increasing. In this research, we will design and build a simple news portal application using API (Application Programming Interface). API is a document consisting of interfaces, functions, classes, structures and other support in application development. With the prototyping method it is hoped that a simple news portal application will be created using NewsAPI which can be freely used. From the results of functional testing using the black box technique, each test case shows that the application is running according to the expected results. The results of non-functional testing using beta testing techniques show that the average percentage value obtained is 86%. The average value for each criterion includes 84% for the Usefulness criterion, 89% for the Ease of Use criterion, 87% for the Ease of Learning criterion, and 84% for the Satisfaction criterion, the highest percentage is for the Ease of Use criterion which proves that the application This portal is easy to use and learn, while also being useful and satisfying for users.